PENGARUH ARUS KAS OPERASI, PERTUMBUHAN PERUSAHAAN, LEVERAGE DAN PROFITABILITAS TERHADAP KONSERVATISME AKUNTANSI - kusuma Indawati Halim (Jurnal Ilmu Akuntansi, 2021)
The principle of conservatism assumes that when choosing between two or more generally accepted accounting techniques, a preference is shown for the choice that has the least favorable impact on shareholder equity. This study attempts to determine the impact of operating cash flow, company growth, leverage, and profitability on accounting conservatism. The population in this study were 52 companies in the consumer goods industry sector on the Indonesia Stock Exchange for the period 2014 to 2018. Sample selection was using purposive sampling and obtained a sample of 36 companies. This type of research is quantitative research. The data analysis technique used is descriptive statistical analysis, classical assumption test, multiple regression analysis, F test, and t test. The test was carried out using the SPSS 22 program. The partial test results show that operating cash flow, company growth, and profitability partially have a positive impact on accounting conservatism, but leverage has no impact on accounting conservatism.